2019
DOI: 10.3389/fpsyg.2018.02627
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spiritual Leadership on Employee Effectiveness: An Intrinsic Motivation Perspective

Abstract: Drawing on spiritual leadership theory and intrinsic motivation theory, we proposed a homologous multilevel model to explore the effectiveness of spiritual leadership on employees’ task performance, knowledge sharing behaviors and innovation behaviors at the individual level. With questionnaires rated by 306 pairs of employees and their supervisors in 26 teams from the energy industry in mainland China, we conduct multilevel analysis to examine our hypotheses. The results show that spiritual leadership was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 78 publications
(107 reference statements)
7
94
0
8
Order By: Relevance
“…In other words, spiritual leaders can create a supportive and friendly environment to help their employees become successful in their work. Previous studies have shown that spiritual leadership is positively related to unit productivity [ 14 ] and employees’ task performance [ 23 ]. As a result, nurses under spiritual leaders are more likely to reach work goals, while the experiences of being successful at work will lead to more engagement in their work [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, spiritual leaders can create a supportive and friendly environment to help their employees become successful in their work. Previous studies have shown that spiritual leadership is positively related to unit productivity [ 14 ] and employees’ task performance [ 23 ]. As a result, nurses under spiritual leaders are more likely to reach work goals, while the experiences of being successful at work will lead to more engagement in their work [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hasil riset ini sesuai dengan penelitian Pio et al, (2015) bahwa terdapat pengaruh positif kepemimpinan spiritual terhadap komitmen organisasional dan kinerja pegawai. Kemudian riset Wang et al, (2019) menemukan kepemimpinan spiritual berhubungan positif dengan kinerja tugas pegawai.…”
Section: Selanjutnyaunclassified
“…Salah satu tugas seorang pegawai dalam melaksanakan tugas dan kewajibannya adalah mengerjakan semua tanggung jawab dengan sebaik-baiknya sebagai kontribusi penilaian supervisor atau kepala pimpinan (Motowidlo dan Van Scotter, Conway, Johnson dalam Wang et al, 2019). Hal yang melatarbelakangi adanya hubungan positif kepemimpinan spiritual terhadap kinerja adalah model kepemimpinan spiritual yang efektif memotivasi dan memberikan semangat bagi pegawai, pemimpin tidak hanya memenuhi kebutuhan dasar pegawai juga memenuhi kebutuhan psikologis serta kebutuhan spiritual yang melingkupi nilainilai spiritual seperti selalu mendekatkan diri kepada Tuhan, kesadaran dalam melaksanakan ibadah menjunjung nilai kejujuran dalam bekerja dan lainnya (Guillén et al, 2015), selain itu pemimpin juga harus mampu melakukan manajemen perusahan dengan baik serta mampu memberikan contoh inspirasi bagi karyawan (Wang et al, 2019).…”
Section: Penelitian Terdahuluunclassified
“…Teachers and principals of schools by using these mechanisms can do educational tasks successfully and desirably and finally support development and realization of noble educational goals. Wang et al (2019) showed in a research that spiritual leadership has positive relation with employee function. Wang et al (2017) concluded that spiritual leadership is a unique approach for preserving organizational resources and reduces the error rate among staff.…”
Section: Introductionmentioning
confidence: 99%